2012
DOI: 10.1016/j.apcatb.2012.08.034
|View full text |Cite
|
Sign up to set email alerts
|

Rational direct synthesis methodology of very active and hydrothermally stable Cu-SAPO-34 molecular sieves for the SCR of NOx

Abstract: A one-pot direct synthesis of Cu-SAPO-34 has been achieved that allows more than 90% yield in the material synthesis. By this method it is easy to control the Cu-loading in the Cu-SAPO-34. It is presented that a maximum in hydrothermal stability with very high activity for NOx SCR with NH 3 is obtained for an optimum Cu loading. KeywordsOne-pot synthesis, silicoaluminophosphate, SAPO-34, selective catalytic reduction (SCR), nitrogen oxides (NOx) Highlights-Rational direct synthesis of Cu-SAPO-34 by using the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
103
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 158 publications
(109 citation statements)
references
References 25 publications
2
103
0
Order By: Relevance
“…[16,18] These results points out the relevance that the new Cu-containing SAPO-18 catalysts may have in the current De-NOx scenario if they show high hydrothermal stability after being treated under severe ageing conditions.…”
Section: -Catalysis and Hydrothermal Stabilitymentioning
confidence: 75%
“…[16,18] These results points out the relevance that the new Cu-containing SAPO-18 catalysts may have in the current De-NOx scenario if they show high hydrothermal stability after being treated under severe ageing conditions.…”
Section: -Catalysis and Hydrothermal Stabilitymentioning
confidence: 75%
“…Recently, it has been described the direct synthesis of Cu-SSZ-13 [13] and other related Cu-containing silicoaluminophosphate materials, such as Cu-SAPO-34 [12d, [14]] and Cu-7 SAPO-18, [15] using the combination of an organometallic Cu-complex (Cu-TEPA) and a cooperative organic molecule as OSDA. Following a similar "one-pot" synthesis procedure combining Cu-TEPA and N,N-dimethyl-3,5-dimethylpiperidinium as cooperative OSDAs, a crystalline Cu-containing SSZ-39 material has been achieved (see supporting information for experimental details and the PXRD pattern of Cu-SSZ-39 in Figure 1).…”
Section: +mentioning
confidence: 99%
“…We and others [9][10][11] have shown that the copper complexes of the linear polyamines triethylenetetramine and tetraethylenepentamine are suitable SDAs for SAPO-34, and that calcination gives active SCR catalysts. Linear polyamines are relatively affordable (compared to the azamacrocycle used in the synthesis of Cu-SAPO STA-7) so we set out to investigate the action of a range of copper complexes of the linear polyamines in the direct synthesis of Cu 2+ -containing SAPOs, and to understand the mechanism by which they direct crystallisation.…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8][9][10][11][12] Calcination then releases the Cu 2+ cations to extra-framework sites distributed throughout the crystals and removes the need for a cation-exchange step. This process was first demonstrated for SAPO STA-7, [6] and subsequently for SSZ-13, [7] SAPO-34, [9][10][11] and very recently for SAPO-18 [12] giving active, selective and hydrothermally stable catalysts. The details of the mechanism by which the calcination of the complex-bearing precursor to SAPO STA-7 gives a porous, acidic framework with dispersed copper cations has been followed by ex situ UV-visible spectroscopy and by in situ microcrystal IR spectroscopy.…”
Section: Introductionmentioning
confidence: 99%